2008
DOI: 10.1099/mic.0.2007/016097-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of microcystin synthetase deletion mutants capable of producing microcystins in strains of the genus Anabaena (Cyanobacteria)

Abstract: Microcystins form a large family of small cyclic heptapeptides harbouring extensive modifications in amino acid residue composition and functional group chemistry. These peptide hepatotoxins contain a range of non-proteinogenic amino acids and unusual peptide bonds, and are typically N-methylated. They are synthesized on large enzyme complexes consisting of non-ribosomal peptide synthetases and polyketide synthases in a variety of distantly related cyanobacterial genera. Here we report a 1236 bp in-frame delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…For the mcy genes, it has been shown that the operon structure and the order of genes varies between the genera Planktothrix, Anabaena and Microcystis (reviewed by Dittmann & Börner, 2005). In addition, recombination between different domains within the mcy gene clusters, point mutations and deletion of gene regions, as well as lack of substrate specificity of A-domains have been shown to contribute to the synthesis of different microcystin isoforms (Fewer et al, 2008;Mikalsen et al, 2003;Tooming-Klunderud et al, 2008). A deletion within the second module of mcyA and the first module of mcyB resulted in the synthesis of another cyanotoxin, nodularin (Moffitt & Neilan, 2004;Rantala et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For the mcy genes, it has been shown that the operon structure and the order of genes varies between the genera Planktothrix, Anabaena and Microcystis (reviewed by Dittmann & Börner, 2005). In addition, recombination between different domains within the mcy gene clusters, point mutations and deletion of gene regions, as well as lack of substrate specificity of A-domains have been shown to contribute to the synthesis of different microcystin isoforms (Fewer et al, 2008;Mikalsen et al, 2003;Tooming-Klunderud et al, 2008). A deletion within the second module of mcyA and the first module of mcyB resulted in the synthesis of another cyanotoxin, nodularin (Moffitt & Neilan, 2004;Rantala et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques allow for an assignment of the actual producer of microcystin and to provide insights into the dynamics of toxin-producing cyanobacteria and environmental regulation of toxins in the field; however, they cannot substitute methods that directly quantify toxins under any circumstances. Bias in each of these different approaches can result from the occurrence of nontoxic mutants in the field that can give rise to false-positive data Fewer et al, 2008) and from variations in the microcystin synthetase sequence that can result in false-negative data (Via-Ordorika et al, 2004;Mbedi et al, 2005). Furthermore, several research groups have established and applied realtime PCR protocols for the quantification of microcystinproducing cyanobacteria (Kurmayer & Kutzenberger, 2003;Vaitomaa et al, 2003;Al-Tebrineh et al, 2011).…”
Section: Detection and Quantification Of Microcystinproducing Cyanobamentioning
confidence: 99%
“…However, a third model and perhaps the most likely explanation for structure of distinct variants is a balance between recombination and positive selection (20). Recombination has been shown to occur in cyanobacteria (21), also involving NRPS genes in strains of both Microcystis, Anabaena, and Planktothrix (22)(23)(24)(25)(26)(27). These recombination events are often associated with changes in the produced microcystin isoforms.…”
mentioning
confidence: 99%